2022
DOI: 10.3390/horticulturae8070641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Growth-Promoting Rhizobacteria Inoculation on the Physiological Response and Productivity Traits of Field-Grown Tomatoes in Hungary

Abstract: Drought-tolerant plant growth-promoting rhizobacteria (PGPR) may promote plant development under limited water supply conditions, when plant’s water demand is not completely satisfied under rain-fed conditions or when irrigation water availability is limited. The aim of this study was to examine the effects of two inoculation treatments (B2: Alcaligenes sp. 3573, Bacillus sp. BAR16, and Bacillus sp. PAR11 strains and B3: Pseudomonas sp. MUS04, Rhodococcus sp. BAR03, and Variovorax sp. BAR04 strains) and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Zhang et al, 2022 reported that Bacillus pumilus inoculation that Streptomyces strains IT25 and C-2012 not only suppressed the signals of stress in tomato plants but also improved plant water in the form of RWC. Nemeskeri et al (2022) stated that inoculation of Pseudomonas sp. MUS04 in tomato plants improved the water uptake and also decreased the plant temperature as compared with noninoculated stressed plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al, 2022 reported that Bacillus pumilus inoculation that Streptomyces strains IT25 and C-2012 not only suppressed the signals of stress in tomato plants but also improved plant water in the form of RWC. Nemeskeri et al (2022) stated that inoculation of Pseudomonas sp. MUS04 in tomato plants improved the water uptake and also decreased the plant temperature as compared with noninoculated stressed plants.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that Streptomyces strains IT25 and C-2012 not only suppressed the signals of stress in tomato plants but also improved plant water status in the form of RWC. Nemeskeri et al. (2022) stated that inoculation of Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nemeskéri et al [10], analyzed the use of plant growth-promoting rhizobacteria (PGPR) to promote tolerance to drought stress in tomato cultivars. Drought-tolerant PGPR may support plant development under limited water supply conditions when the plant's water demand is not completely satisfied under rain-fed conditions or when the availability of irrigation water is limited.…”
mentioning
confidence: 99%